Transition metal oxide (TMO) thin film memristor on cu substrate using dilute electrodeposition method - Fauzi, Fatin Bazilah; Othman, Raihan; Mohamed, Mohd Ambri; Herman, Sukreen Hana; Ahmad Azhar, Ahmad Zahirani; Ani, Mohd Hanafi (Japan Institute of Metals, 2015)
Instead of titanium dioxide (TiO2), many researches have been done to explore the compatibility of zinc oxide (ZnO) to be used as the active layer of memristor. In this study, an Au/ZnO-Cu2O-CuO/Cu memristor was fabricated using dilute electrodeposition and subsequently thermal oxidation. The XRD result indicates that Zn was oxidized to ZnO and has a wurzite structure while copper (Cu) substrate was also oxidized to copper (I) oxide (Cu2O) and copper (II) oxide (CuO). The surface morphology of ZnO shows the formation of needle-like structure on the surface after the thermal oxidation process. 15 s deposited ZnO-Cu2O-CuO gave the thinnest film of 81 nm with largest value of resistance difference of 14.11 k3 and resistive switching ratio of 3.76. Empirical study on thermodynamics of metal oxides and diffusivity of Zn2+ and O21 in ZnO shows that the structure is formed due to the difference of diffusivity of each species during the thermal oxidation process. The synthesized Au/ZnO-Cu2O-CuO/Cu memristor shows a potential application in production of a non-complex and low cost memristor.